2001
DOI: 10.1128/aac.45.4.1298-1301.2001
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activities of Milk Lipids

Abstract: The bactericidal capacity of digestion products of bovine milk triglycerides and membrane lipids was tested in vitro using Escherichia coli O157:H7, Salmonella enteritidis, Campylobacter jejuni, Listeria monocytogenes, and Clostridium perfringens. C 10:0 and C 12:0 fatty acids and digestion products of sphingolipids appeared to be effective bactericidal agents, whereas digestion products of phosphoglycerides were moderately bactericidal. Thus, milk fat sphingolipids and triglycerides, particularly those contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
148
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(153 citation statements)
references
References 25 publications
2
148
0
Order By: Relevance
“…The results suggested that the activity of the castor oil could be due to the mixture of fatty acids. Fatty acids, as well as their corresponding salts, have been reported to display the antimicrobial activity (Nieman 1995;Sprong et al 2001;Skrivanova et al 2005). Despite the lack of elements which would make the inhibitory mechanism fully understood, it has been assumed that the fatty acids penetrate the lipid membrane and dissociate in the more alkaline interior causing the metabolic uncoupling (Russell and Diaz-Gonzalez 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that the activity of the castor oil could be due to the mixture of fatty acids. Fatty acids, as well as their corresponding salts, have been reported to display the antimicrobial activity (Nieman 1995;Sprong et al 2001;Skrivanova et al 2005). Despite the lack of elements which would make the inhibitory mechanism fully understood, it has been assumed that the fatty acids penetrate the lipid membrane and dissociate in the more alkaline interior causing the metabolic uncoupling (Russell and Diaz-Gonzalez 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Gut dysbiosis has been linked with endotoxin-mediated chronic disease in mouse models [51,52]. Sphingosine, a hydrolytic product of dietary SM, is known to have bactericidal effects [53]. We have previously reported that supplementation of 0.25% (w/w) milk SM to HFD-fed mice altered the fecal microbiota composition by reducing Gram-negative bacterial phyla and increasing Bifidobacterium [28].…”
Section: Discussionmentioning
confidence: 99%
“…chain length, and on the microbial strain involved. Generally, Gram-positive bacteria are more sensitive whereas Gram-negative bacteria are not (Sprong et al 2001). This phenomenon may be caused by the difference between the outer membrane of the cell wall of Gram-positive and Gram-negative bacteria (Sun et al 2003).…”
mentioning
confidence: 99%